Teori belajar humanistik dalam perspektif religius - Romelah romelah; nurul mawaridah nurul (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The Qur'an and Hadith, which are religiously the guidelines for Muslim for the development of various sciences, including education and psychology. Innovations in fields of scientific development are carried out based on the perspective of religius. Therefore, the purpose of writing this article is to understand the nature of learning according to humanistic theory and the implementation of humanistic theory from a religious perspective. This study uses a qualitative approach and as the library research by connecting the texts in the Qur'an and Hadith that explain humanistic theory and its implementation based on a religious perspective. The essence of learning according to humanistic theory focuses on the learning process and not on learning outcomes that carry the concept of humanizing humans so that they will understand themselves and their environment. The implementation of the humanistic theory of a religious perspective related to the problem of punishment about praying education in the hadith narrated by Abu Dawud. The humanistic in the Qur'an is stated in QS. Al-Baqarah: 256 and QS. Al-Kahf: 29 about the freedom to choose to believe or not.